(untitled) (Journal of the College of Basic Education, 2023)
Conclusion. The purpose of this study is the cognitive assessment of the daily disturbances thatstudents are exposed to in their daily lives, and the sample of this study was 157 male and female students.62) male; (95 females) from the scientific and humanities departments in the College of Education at the UniversityAl-Mustansiriya. The results of applying the inconvenience assessment scale for college students - the sub-scalepertaining to the cognitive assessment of daily disturbances, that these disturbances are threatening.The results of the study show that there is no major or interactive effect of the current research variables, which is gender.and academic specialization.